United Arab Emirates (UAE): A scientometric assessment of Covid-19 publications - Gupta, B. M.; Dhawan, S.M.; Kappi, Mallikarjun (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. The United Arab Emirates continues to undertake and sustain its research pursuits in Covid-19 as a matter of strategy, considering that the country is facing unique challenges in this area of research. The paper seeks to analyze UAE publications on Covid-19 research and describe its research trends. Methodology. A literature search on UAE publications on Covid-19 was conducted using the Scopus database, limiting the search period for the study to December 1, 2019 - April 7, 2023. Data were retrieved and downloaded for analysis using Microsoft Excel and Scopus Citation Overview tools. VOSviewer software was used to provide creative visualization of the relationships across researchers, institutions, and journals that reported UAE publications. Results: 48,1461 publications were published on Covid-19 from December 2019 till April 7, 2023. Of these, the UAE contributed 3402 publications, constituting 0.71% share of global output and registered 14.63 average citations per article (CPP). The 732 (21.52%) UAE papers had received external funding support, and another 2493 (73.28%) papers appeared through international collaboration with countries such as the U.K (n=556), USA (n=553), India (n=448), and Saudi Arabia (n=399). The leading UAE participating organizations in Covid-19 research include the University of Sharjah (n=619), United Arab Emirates University (n=520), and Zayed University (n=239). The organizations which made the most citation impact in terms of CPP and RCI include American University in the Emirates (40.54 and 3.34), Mohammed Bin Rashid University of Medical & Health Sciences (34.4 and 2.83), and Al Jalila Children’s Specialty Hospital (31.88 and 2.62). The leading UAE participating authors in Covid-19 research include R. Halwani (n=83), Z. Umar (n=38), and Q. Hamid (n=37). The authors who made the most citation impact in terms of CPP and RCI include R. Halwani (52.61 and 4.33), H.Q. Al Shamsi (30.24 and 2.49) and A.S. Al Dhaheri (28.81 and 2.37). The most utilized channels of research communication in Covid-19 research include PLOS One (n=73), International Journal of Environmental Research & Public Health (n=46), and Scientific Reports (n=36). The journals which received the most citations for UAE papers on Covid-19 research include the International Journal of Infectious Diseases (30.56 CPP), IEEE Access (20.49 CPP), and Frontiers in Psychiatry (17.40 CPP). Conclusion: The study presents the current status of research and the publication trends in Covid-19 in the UAE, particularly its most used sources for research publication, most productive and most cited organizations and authors, and its most sought-after topics in Covid-19 research. Strengthening research collaboration between UAE and the Middle East countries and with the developed world countries will further help UAE improve the quality and quantity of its research on Covid-19 and help implement its Covid-19 policies in the region.